Synthesis and Characterization of Ordered and Disordered Mesoporous Alumina as High-Performance Molybdenum-99 Adsorbents - I. Saptiama; F. Rindiyantono; A. Aries; Y. V. Kaneti; M. Iqbal (Atom Indonesia, 2021)
Molybdenum-99 (99Mo) is the parent radioisotope of technetium-99m (99mTc),an essential medical radioisotope for diagnostic agents in nuclear medicine.In 99Mo/99mTc generator, a chromatography column system with 99Mo adsorbent as afiller is usually used to produce 99mTc in hospitals. However, it is still challenging to find high-performance adsorbentsfor Mo adsorption.We have synthesized both ordered and disordered mesoporous alumina and compared their performance as 99Mo adsorbents. These materials were prepared via a soft-templated method using a triblock copolymer as the template, followed by air calcination at 400°C.The amount of nitric acid (HNO3) and the drying time were adjusted systematically to synthesize the ordered mesoporous alumina. The obtained ordered and disordered mesoporous alumina were characterized by low-and wide-angle X-ray diffractions (XRD), nitrogen adsorption-desorption, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The 99Mo adsorption capacities of these materials were evaluated by using the batch method. The experimental results show that the ordered mesoporous alumina hasa higher 99Mo adsorption capacity of 72.06 mg(Mo)g-1 than the disordered mesoporous alumina (50.12 mg(Mo)g-1). The results indicate the excellent potential of ordered mesoporous alumina as an adsorbent for the 99Mo/99mTc generator column.